2016
DOI: 10.1080/17430437.2016.1225882
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion in sport: disability and participation

Abstract: For the last couple of decades UNESCO has aimed to achieve to a far extent the implementation of the guiding principle of inclusion at all levels in education systems worldwide. The idea that countries 'should ensure an inclusive education system at all levels' is also a central objective of the UN Convention on the Rights of Persons with Disabilities. This Introduction to the Special Issue explores what participation as an aspect of inclusion means in general, and realistically can mean in sport and quality p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
92
0
26

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 31 publications
4
92
0
26
Order By: Relevance
“…Differently from those contexts, nonparticipation in sport is not equivalent to social exclusion, which would be the case if people wanted to participate but could not. Inclusion in sport should consider guaranteeing access, improving participation, and offering a continuum of opportunities for people with impairments [58]. This argument is in line with the UN Convention that stated that the states should encourage a twin-track approach to sport participation, in both mainstream sport with necessary adaptations and in parasport.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Differently from those contexts, nonparticipation in sport is not equivalent to social exclusion, which would be the case if people wanted to participate but could not. Inclusion in sport should consider guaranteeing access, improving participation, and offering a continuum of opportunities for people with impairments [58]. This argument is in line with the UN Convention that stated that the states should encourage a twin-track approach to sport participation, in both mainstream sport with necessary adaptations and in parasport.…”
Section: Discussionmentioning
confidence: 74%
“…The analysis of the recent inclusion debates in sport helps the argument that inclusion in sport is distinct from inclusion in other contexts, for example, in education and workplace [58]. Differently from those contexts, nonparticipation in sport is not equivalent to social exclusion, which would be the case if people wanted to participate but could not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An estimated 6% of people in the UK have some form of neurological motor disorder (MacDonald, Cockerell, Sander, & Shorvon, 2000), which affects participation in healthrelated activities and poses a challenge for society to promote health and wellbeing of all its members (Coates & Vickerman, 2010;Kiuppis, 2018) Indeed, it is reported that 70-75% of disabled people do not participate in any sport or physical activity (Sport England, 2013) and this increases the risk of developing cardiovascular and metabolic diseases (Ryan, Crowley, Hensey, Broderick, McGahey, & Gormley, 2014), muscle weakness (Wiley & Damiano, 1998) and reduced bone density (Cohen, Lahat, Bistritzer, Livne, Heyman, & Rachmiel, 2009). Few sports currently exist for those with a severe neurological disability, and these are often limited to low levels of aerobic demand and weight bearing demands (Van der Linden, Jahed, Tennant, & Verheul, 2018).…”
Section: Introductionmentioning
confidence: 99%